THE FACTORS THAT CAUSE THE LOSE OF ABILITY IN USING SUNDANESE OF ENGLISH LITERATURE STUDENTS IN UNIVERSITAS GUNADARMA - Rangga, Pradheka Aria (Universitas Gunadarma, 2018)
In sociolinguistics, there is a phenomenon in which a community stops using their parent’s heritage language by making the use of the language in which they are located or stay as a mean of communication, it is called as a language shift. In this research, it aims to find out the factors that affected the students whose parents originated from Sunda not interested to learn their parent’s heritage language. Moreover, it aims to find out the most dominant factor that affected the students not interested to learn their parent’s heritage language. This research used the qualitative method and the data source comes from the students of English literature in Universitas Gunadarma. The result of this research shows the factors that affected the students not interested to learn their parent’s heritage language such as social, economic, and political factor, demographic factor, attitudes and values factors, education factor, migration factor, and bilingual or multilingual factors. Furthermore, education factor is assumed as the most dominant or influential factor to the students not interested to learn their parent’s heritage language, because all of the students choose agree to the education factor.